Answer:
Step-by-step explanation:
Let the larger integer = 2x + 1
Let the second integer = 2x - 1
1/2 (2x + 1 + 2x - 1) = - 12 Combine the left
1/2(4x) = - 12 Combine 1/2 (4x)
2x = - 12 Divide by 2
2x/2 = - 12/2
x = - 6
2x + 1 = 2*-6 + 1 = -11
2x - 1 = 2*-6 - 1 = - 13
Check
-11 + - 13 = - 24
1/2(-24) = -12 which checks.
Answer: 0.336
Step-by-step explanation:
n=7
r=2,1,0
p=44%=0.44
q=1-0.44=0.56
7C2(0.44)^2(0.55)^5 +
7C1(0.44)^1(0.56)^6 +
7C0(0.44)^0(0.56)^7
Evaluate:
0.2239055109+
0.0949902167 +
0.0172709485
Sum: 0.33617= 0.336
It’s c
-10, -9, -8
Sawarasenai kimi wa shojo na no!~ boku wa yarichin bicchi no osu dayo! ah~
Answer:
<em>102°</em>
Step-by-step explanation:
(3x - 12)° + (2x + 2)° = 180°
5x - 10 = 180 ⇒ x = 38
m∠A = (3x - 12)°
<em>m∠A</em> = (3×38 - 12)° = <em>102°</em>
The answer to 10+10 is 20. I hope I made it for the dog.